Beyond serotonin: newer antidepressants in the future. (3rd August 2017) - Rakesh, Gopalkumar; Pae, Chi-Un; Masand, Prakash S.
ABSTRACT: Introduction : There are numerous antidepressants for the treatment of major depressive disorder (MDD) on the market. However, inadequate treatment response, therapeutic lag between drug administration and the onset of clinical improvement, and safety/tolerability issues with the use of contemporary antidepressants have accelerated the search for newer antidepressants with novel mechanisms of action. Areas covered : The authors review novel antidepressants with rapid efficacy for diverse MDD symptoms and have fewer adverse effects (AEs). Mechanisms of action for novel therapeutic molecules are through glutamatergic, opiate, cholinergic receptors and neuroplasticity. We enumerate results from human trials with novel agents in all phases, highlighting proximity to approval and therapeutic potential based on quality of evidence. Expert commentary : There is a huge unmet need to diversify conventional antidepressant targets. Glutamatergic and opiate agents may be most promising among newer therapeutic agents. It is also important to develop advanced but flexible synergistic treatment strategies with newer therapeutic agents that are usable in routine clinical practice. This would include combining newer molecules with existing antidepressants and using molecules that target specific symptom dimensions of MDD. These strategies would lead to a systematic approach to tackle treatment resistant depression (TRD) and treatment of residual symptoms in partially remitted MDD.